Peroxisome Proliferator-activated Receptor γ Activation by Ligands and Dephosphorylation Induces Proprotein Convertase Subtilisin Kexin Type 9 and Low Density Lipoprotein Receptor Expression - Duan, Yajun (American Society for Biochemistry and Molecular Biology, 2012)
Proprotein convertase subtilisin kexin type 9 (PCSK9) plays an important role in cholesterol homeostasis by enhancing the degradation of LDL receptor (LDLR) protein. Peroxisome proliferator-activated receptor γ (PPARγ) has been shown to be atheroprotective. PPARγ can be activated by ligands and/or dephosphorylation with ERK1/2 inhibitors. The effect of PPARγ on PCSK9 and LDLR expression remains unknown. In this study, we investigated the effects of PPARγ on PCSK9 and LDLR expression. At the cellular levels, PPARγ ligands induced PCSK9 mRNA and protein expression in HepG2 cells. PCSK9 expression was induced by inhibition of ERK1/2 activity but inhibited by ERK1/2 activation. The mutagenic study and promoter activity assay suggested that the induction of PCSK9 expression by ERK1/2 inhibitors was tightly linked to PPARγ dephosphorylation. However, PPARγ activation by ligands or ERK1/2 inhibitors induced hepatic LDLR expression. The promoter assay indicated that the induction of LDLR expression by PPARγ was sterol regulatory element-dependent because PPARγ enhanced sterol regulatory element-binding protein 2 (SREBP2) processing. In vivo, administration of pioglitazone or U0126 alone increased PCSK9 expression in mouse liver but had little effect on PCSK9 secretion. However, the co-treatment of pioglitazone and U0126 enhanced both PCSK9 expression and secretion. Similar to in vitro, the increased PCSK9 expression by pioglitazone and/or U0126 did not result in decreased LDLR expression and function. In contrast, pioglitazone and/or U0126 increased LDLR protein expression and membrane translocation, SREBP2 processing, and CYP7A1 expression in the liver, which led to decreased total and LDL cholesterol levels in serum. Our results indicate that although PPARγ activation increased PCSK9 expression, PPARγ activation induced LDLR and CYP7A1 expression that enhanced LDL cholesterol metabolism.